Study on Factors Influencing College Students’ Mental Health - Chen, Junhong (International Journal of Social Sciences and Public Administration, 2024)
Taking the mental health of college students as the research object, this paper discusses the family factors, personal factors, school factors and social factors affecting the mental health of college students. It is concluded that family education and family atmosphere in family factors, personality characteristics and ability to cope with stress in individual factors, education mode and psychological counseling services in school factors, and social support and social environment in social factors all have an impact on college students’ mental health. This study provides theoretical basis and practical guidance for college students’ mental health education, which is of great significance for promoting college students’ mental health.